Role of Live Microbes for Fermentation and Enhancement of Feeding Value of Wheat Straw as Animal Fodder - Feyisa, Misikir Mengistu; Yadav, Praveen (The Asia Journal of Applied Microbiology, 2021)
Nowadays, a resource terrible and technologically hungered farmhand within the developing nations of tropical zones faces intense challenges of their livestock farming and products due to tremendously and seriously increments of the human populace in this century. These challenges create this potential to feed human food security and not meet this sector’s 2050 human population demand. The farmer faces the challenges of creating better value and sufficient harvests. Their livestock’s low-fine feedstuff-like crop-residues with low dietary due to shrinking grazing land shifted to farming land. Hence, our farmers want the generation that tackles this hassle through biological treatment to get without difficulty digested, nicely evolved flavor and nutritionally in shape, extra protein content in flip offers proper milk and red meat in-phrases of high-class besides capacity. This study aimed to determine the nutritional worth of wheat chaff treated biologically by bacterial and fungal Lactobacillus Casei Shirota and Aspergillus Niger strain. It also analyzed the physical and chemical structure of fermented chaff to obtain the numerical values that indicate the increments straw value and enhance feed intake of the individual livestock.